Kenaf oil methyl esters - Knothe, Gerhard (Animo Repository, 2013)
Additional or alternative feedstocks are one of the major areas of interest regarding biodiesel. In this paper, the fuel properties of kenaf (Hibiscus cannabinus L.) seed oil methyl esters are comprehensively reported. This biodiesel is also relatively unique by containing small amounts of cyclic fatty acid methyl esters and of methyl epoxyoleate. Biodiesel from kenaf seed oil generally meets fuel property specifications in biodiesel standards. No influence of either the methyl esters of epoxyoleic acid or the cyclic fatty acids on fuel properties was detected at the levels present in kenaf, however, the kinematic viscosity was moderately higher than could be expected, indicating that cyclic moieties may increase viscosity. The 1H- and 13C-NMR spectra of kenaf seed oil methyl esters are also discussed. © 2013.